Key creative industry analysis using input-output approach - Efriyani Sumastuti; Ika Indriasari (Journal of Innovation in Business and Economics, 2025)
This study examines the impact of GoFood, a culinary delivery service, on various economic sectors in Indonesia, with a particular focus on empowering micro, small, and medium enterprises (MSMEs). The rise of the sharing economy, driven by digital platforms such as GoFood, has significantly reshaped traditional business models. Employing an input-output analysis, this research assesses GoFood’s influence on economic growth and sectoral interdependencies. Data from the Creative Economy Agency's input-output table, developed in collaboration with BPS, were used to analyze economic linkages and demand structures. The results show that intermediate demand is primarily driven by the mining, coal, and oil and gas sectors, while final demand is dominated by the construction sector. The food and beverage industry emerges as a strategic sector. Strengthening this industry—supported by platforms like GoFood—can play a crucial role in boosting economic growth and enhancing inter-sectoral connectivity. These findings highlight the importance of multi-stakeholder collaboration to maximize the culinary sector’s contribution to the national economy.